The English Department Students' Perception Toward Teaching Skills Through the Implementation of Kampus Mengajar Program - Ayu Oktaviana Sipahutar; Lastri Wahyuni Manurung; Usman Sidabutar; Eka Putri Saptari Wulan (Innovative: Journal Of Social Science Research, 2023)
This study aimed to know the English Department students’ perception toward teaching skills through the implementation of Kampus Mengajar program. There were 26 of the English Department students. This study used a descriptive qualitative design. The researcher used questionnaire to collect the data, the Likert Scale. The result of this study showed that the English Department students’ perception are positive, as many as 15 students (55,77%) of the 26 English Department students, this shows that more than half of the English Department students’ perception related to skills of opening and closing the lesson, 14 students (53,85%)related to explaining skills, 15 students (55,77%) related to variation skills, 13 students (51,92%) related to questioning skills, 13 students (51,28%) related to reinforcement skills, 17 students (64,10%) related to class management skills, 13 students (50%) related to small group teaching skills, and 15 students (55,77%) related to skills of guide small group discussion. The researcher concluded that the English Department students’ perception toward teaching skills through the implementation of Kampus Mengajar program are positiv